Children and the climate migration crisis : a casebook for global climate action in practice and policy - Cardarelli, Rose; Pomper, Harley (Emerald Publishing Limited, 2024)
With climate disasters expected to displace millions as the planet continues to warm, we are fast approaching a serious humanitarian crisis. Foregrounding how our children are increasingly shouldering the era-defining effects of climate change, Children and the Climate Migration Crisis chronicles our collective responsibility to address resulting consequences for the wellbeing and future of children everywhere. Using illustrative case studies to dive deeper into the current situation, Rose Cardarelli and Harley Pomper outline an educational response for mitigating climate migration and stress-related trauma, including how to foster the development of the social and emotional strengths and responses that children need to grapple with a world in jeopardy. Subverting eco-anxiety and establishing ways we can empower children around the globe, Children and the Climate Migration Crisis takes a holistic approach to bring together the relevancy and impact of forced migration and climate resilience, underpinned by a social emotional approach to overall wellbeing, adjustment, and adaptability.